2022
DOI: 10.1111/ecog.06113
|View full text |Cite
|
Sign up to set email alerts
|

Can we model distribution of population abundance from wildlife–vehicles collision data?

Abstract: Reliable estimates of the distribution of species abundance are a key element in wildlife studies, but such information is usually difficult to obtain for large spatial or long temporal scales. Wildlife–vehicle collision (WVC) data is systematically registered in many countries and could be used as a proxy of population abundance if the number of WVC in each territory increase with the population abundance. However, factors such as road density or human population should be controlled to obtain accurate abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…We found that roadkill mortality varies throughout the year, with different patterns for each vertebrate class, the peak of collisions coinciding with suitable environmental conditions for each group, when they are most active (Garriga et al 2017;Fernández-López et al 2022). Of the 413 carcasses recorded, mammals were the most run over, with 189 animals killed on the road (45.76% of the total).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…We found that roadkill mortality varies throughout the year, with different patterns for each vertebrate class, the peak of collisions coinciding with suitable environmental conditions for each group, when they are most active (Garriga et al 2017;Fernández-López et al 2022). Of the 413 carcasses recorded, mammals were the most run over, with 189 animals killed on the road (45.76% of the total).…”
Section: Discussionmentioning
confidence: 90%
“…To analyse whether the number of accidents depended on road tortuosity and the presence of fencing (i.e. characteristics of the road), we fitted an N-mixture hierarchical model (Royle and Nichols 2003;Fernández-López et al 2022) using the unmarked package (Fiske and Chandler 2011). In the N-mixture model, we considered the repeated monthly sampling (12 months) of the 10 road sections, the effect of the presence of fence (fenced vs unfenced) on the animal abundance, and the additive effects of tortuosity (scaled values of this continuous variable) and presence of fence as covariates modelling the detectability of roadkill events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Passive surveillance can be enhanced: for instance, by increasing effort to detect and collect road kills (Grilo et al 2020;Fernández-López et al 2022), which can be risk based (e.g., attending to areas of more likely introduction of pathogens).…”
Section: Characteristics Of Wild Ruminants Relevant To Early Detectio...mentioning
confidence: 99%